Determining Key Factors of Customer Satisfaction and Repurchase Intention for Azarine Cosmetic on Shopee - Noviandari, Sandra Rosa; Fachrodji, Achmad (Journal of Applied Business, Taxation and Economics Research, 2024)
With the development of the beauty industry, especially in the realm of local products, companies need to maintain customer loyalty. This study aims to evaluate the relationship between EWOM, brand image, product quality, and price perception that influence repurchase intentions and their impact on customer satisfaction of the Azarine Cosmetic brand on the Shopee platform. Using a quantitative approach, this study involved 135 respondents in Jabodetabek who have used Azarine products and purchased them on Shopee at least once. The data analysis method used was Structure Equation Modeling-Partial Least Squares (SEM-PLS). The study results indicate that product quality and price perception have a significant impact on customer satisfaction and repurchase intention. Meanwhile, EWOM and brand image do not have a significant impact on customer satisfaction and repurchase intention. Customer satisfaction also significantly affects repurchase intention. Customer satisfaction partially mediates the relationship between product quality and repurchase intention, but does not mediate the relationship between EWOM, brand image, and price perception on repurchase intention.